Marriage and Social Status Complication in Jane Austen’s Emma Compared to Millennials’ Perspectives - Desi Anggerina Hikmaharyanti, Putu; Sri Rwa Jayantini, I Gusti Agung (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Marriage and social status always are intertwined in human life. Both are reflected on Jane Austen’s setting of the novel Emma when Victorian era had strong belief on marriage with the same social class which was dominantly shown in upper class people. The problem found in the novel is how social status influences people to decide with whom they will marry. In line with that situation, millennial generation (born in 1981-1996) also has nearly similar point of views related to marriage and social status in their life discussed in this study. By analyzing the data qualitatively, this study raised the specific conditions about marriage and social status experienced by the novel characters and millennial generations based on a research survey. Three couples in the novel experienced their marriage stunted by different social class between lower and upper class. Meanwhile, after conducting a survey to the millennial correspondents, most of them agreed that marriage is important and 33.3 % correspondents have no concern to social status. About 58.3% correspondents thought that marrying someone with the same social status is happier. Moreover, 66.7% voted that social status influences someone to decide with whom they will marry.